Cogestão de contratações públicas: estudo em uma organização do Exército Brasileiro - Fernandes, Evandro Missagia (2024)
This study addresses co-management of public procurement as a way of rationalizing, optimizing and improving the process, aiming at efficiency, effectiveness and efficacy in the provision of public services. Public procurement plays a crucial role in contemporary States, establishing agreements between governments and private entities to optimize resources and improve the quality of services. This work is being guided by the following research problem: how co-management of public contracts can contribute to improving public procurement processes in military organizations of the Brazilian Army. To obtain answers to this problem, the general objective was to evaluate the public procurement carried out by the Administrative Base of the Santa Maria Garrison (B Adm Gu SM) in co-management with other military organizations in the region, in the period after its implementation. The specific objectives are: to characterize the implementation of the public procurement management process in B Adm Gu SM, to study the public contracts signed by B Adm Gu SM and other OM, considering constructs from the literature and to analyze the advantages and disadvantages of the structure implemented for the management of the acquisition process, management and supervision of contracts. This is applied research, descriptive in nature with a deductive method. The research was conducted as a case study, employing triangulation of information and quantitative and qualitative approaches in data collection. Bibliographic, documentary and semi-structured interview research were carried out to obtain a comprehensive and in-depth view of the hybrid management model of public contracts at B Adm Gu SM. Data were collected through primary and secondary sources. Data analysis was performed using techniques such as Descending Hierarchical Classification (DHC), Correspondence Factor Analysis (CFA) and Similitude Analysis (ASim), providing a detailed understanding of the results obtained from the qualitative data and a descriptive analysis (quantities, description, percentages and means) for the quantitative data. The results indicated that the co-management model implemented by B Adm Gu SM promoted advances in the efficiency and organization of public procurement, which enhanced administrative control, cost reduction and standardization of processes. The main theoretical contributions of the study were the demonstration of how the dimensions of the hybrid model — process economy, control and monitoring, transparency and accountability, and development of expertise — operate in an interdependent and complementary manner. These dimensions reinforce each other, creating a virtuous cycle that increases the efficiency of the contract management model. However, the study identified challenges which still require adjustments. It was concluded that the model is replicable in other public organizations, as long as adjustments are made to overcome these bottlenecks, consolidating its capacity to optimize resources, improve the quality of services, and align with best practices in public management and governance.